Digital Consumer Insight untuk Membangun Promosi bagi UKM di Lingkungan Tangerang Kota - Dwityas, Nindyta Aisyah; Hesti, Sri (LPkM Universitas Bakrie, 2021)
Educational activities about digital consumer insight to build SME promotions in the Tangerang City environment are carried out to help micro and small-scale businesses in the Tangerang City environment to develop the businesses they run. This activity was attended by 22 participants and was held in Cibodas Village in March 2020. The method used is 1) counseling and introduction to online business development, especially regarding consumer behavior in the digital era, 2) education about the activities and stages that consumers go through in making purchase decisions on various online platforms, 3) tutorials for consumers targeting on online platforms, 4) tutorials on utilizing the results of analysis of consumer information to develop marketing communication strategies in online platforms, 5) interactive discussions, and 6) evaluation. In particular, business development is focused on promotional activities on online platforms by utilizing information about consumer behavior in the digital era. This information is the result of previous research on the